1984
DOI: 10.1002/tea.3660210809
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between science process abilities of teachers and science achievement of students: An experimental study

Abstract: The objective of this experimental study is to investigate the relationships among science teacher characteristics and student outcomes. The selected characteristics of teachers are their understanding of science processes and their ability to control variables, and the outcomes of students are the achievement in science contents and processes. The results support the hypothesized relationships and show that the teacher ability to control variables is a more valuable characteristic than the understanding of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The emphasis on science process skills in elementary science curricula since the 1960s has made the acquisition of science process skills one of the major goals of teacher preparation programs. Several studies have indicated that teachers who are proficient in process skills use strategies that give children opportunities to learn those skills (Ashley & Butts, 1972;Butts & Raun, 1969;Jaus, 1975) and other studies have shown that teacher knowledge of science processes is positively related to student achievement (Aiello-Nicosia, Sperandeo-Mineo, & Valenza, 1984;Lawrence, 1975). In view of these theoretical and empirical considerations, the literature on the relative effectiveness of different strategies for teaching process skills to preservice elementary teachers is surprisingly limited.…”
mentioning
confidence: 99%
“…The emphasis on science process skills in elementary science curricula since the 1960s has made the acquisition of science process skills one of the major goals of teacher preparation programs. Several studies have indicated that teachers who are proficient in process skills use strategies that give children opportunities to learn those skills (Ashley & Butts, 1972;Butts & Raun, 1969;Jaus, 1975) and other studies have shown that teacher knowledge of science processes is positively related to student achievement (Aiello-Nicosia, Sperandeo-Mineo, & Valenza, 1984;Lawrence, 1975). In view of these theoretical and empirical considerations, the literature on the relative effectiveness of different strategies for teaching process skills to preservice elementary teachers is surprisingly limited.…”
mentioning
confidence: 99%
“…As reported in previous research, teachers who have poor conceptual knowledge of SPS are less equipped to use inquiry teaching and related learning strategies in their classrooms (Anderson 2002). If understanding of SPS is not emphasized in teacher education programs, there is a high likelihood that students will also have the wrong conceptions about these skills as previous studies show that there is a correlation between the level of understanding and mastery of SPS among teachers with the level of students' understanding and mastery of SPS (Aiello-Nicosia, Sperandeo and Valenza 1984). The practical implementation of science in schools also will continue to produce students who follow instructions and achieve high scores without an understanding of the SPS that they use in carrying out the practices of science.…”
Section: Discussionmentioning
confidence: 90%
“…The condition to indicate that the teacher has not fully optimize science process skill in the learning process. The low students' learning outcomes associated with the low teachers' ability in the mastery of science process skill [10]. In addition, students who obtaining low scores of science process skill test due to rarely do laboratory-based learning activities [11].…”
Section: Resultsmentioning
confidence: 99%